Supercritical CO2extraction of caraway (Carum carvi L.) seed: Optimization and parametric interaction studies using design of experiments - Shrirame B.; Geed S.R.; Hassan S.Z.; Verma J.S.; Samal K.; Namdeo A.; Rai B.N. (My University, 2025)
The essential oil of caraway seed finds its important application in pharmaceutical industries due to its antioxidant, antibacterial, fungicidal, and insecticidal activity. The present study investigates the supercritical CO2 (SC-CO2) extraction of essential oil from caraway seeds. The SC-CO2 extraction process parameters were optimized, and the properties of extracted essential oil were characterized. Experiments were designed using the design of experiments methods to investigate the effects of operating pressure, temperature, and CO2 flow rate on the essential oil yield. A sequential approach in designing of experiments was applied. The optimization results show that higher pressure plays a vital role in deciding the oil yield. The maximum yield (3.62%) for caraway seed oil was obtained at 350 bar pressure, 35°C temperature, and 14 g/min solvent flow rate. The FT-IR and qualitative GC-MS analysis of extracted oil (based on % area) resulted that caraway seeds are a good source of Octadec-9-enoic acid (39.05%) and (R)-Carvone (11.08%). © 2022 Elsevier Ltd.